Mechanism of formation of competitiveness of non-Olympic sports - Sereda, N. (Slobozhanskyi herald of science and sport, 2018)
The article analyzes the competitiveness of non-Olympic sports in Kharkiv. A mechanism for the formation of competitiveness non-Olympic sports are proposed.